RETRACTED: Allopregnanolone Modulates GABAAR-Dependent CaMKIIδ3 and BDNF to Protect SH-SY5Y Cells Against 6-OHDA-Induced Damage - Wang, Tongtong; Ye, Xin; Bian, Wei; Chen, Zhichi; Du, Juanjuan; Li, Mengyi; Zhou, Peng; Cui, Huairui; Ding, Yu-Qiang; Qi, Shuangshuang; Liao, Min; Sun, Chenyou (Frontiers in Cellular Neuroscience, 2020)
Allopregnanolone (APα), as a functional neurosteroid, exhibits the neuroprotective effect on the neurodegenerative diseases such as Parkinson’s disease (PD) through γ-aminobutyric acid A receptor (GABAAR), but it has not been completely understood about its molecular mechanisms. In order to investigate the neuroprotective effect of APα, as well as to clarify its possible molecular mechanisms, SH-SY5Y neuronal cell lines were incubated with 6-hydroxydopamine (6-OHDA), which has been widely used as an in vitro model for PD, along with APα alone or in combination with GABAAR antagonist (bicuculline, Bic), intracellular Ca2+ chelator (EGTA) and voltage-gated L-type Ca2+ channel blocker (Nifedipine). The viability, proliferation and differentiation of SH-SY5Y cells, the expression levels of calmodulin (CaM), Ca2+/calmodulin-dependent protein kinase II δ3 (CaMKIIδ3), cyclin-dependent kinase-1 (CDK1) and brain-derived neurotrophic factor (BDNF), as well as the interaction between CaMKIIδ3 and CDK1 or BDNF were detected by morphological and molecular biological methodology. Our results found that the cell viability and the number of tyrosine hydroxylase (TH), bromodeoxyuridine (BrdU) and TH/BrdU-positive cells in 6-OHDA-treated SH-SY5Y cells were significantly decreased with the concomitant reduction in the expression levels of aforementioned proteins, which were ameliorated following APα administration. In addition, Bic could further increase the number of TH or BrdU-positive cells as well as the expression levels of aforementioned proteins except for TH/BrdU-double positive cells, while EGTA and Nifedipine could attenuate the expression levels of CaM, CaMKIIδ3 and BDNF. Moreover, there existed a direct interaction between CaMKIIδ3 and CDK1 or BDNF. As a result, APα-induced an increase in the number of TH-positive SH-SY5Y cells might be mediated through GABAAR via Ca2+/CaM/CaMKIIδ3/BDNF (CDK1) signaling pathway, which would ultimately facilitate to elucidate PD pathogenesis and hold a promise as an alternate therapeutic target for PD.